A Study on Equivalence in the Indonesian-English Translation of Ismail’s Selected Poems - Oktaviani, Faradila; Putri, Sigfrieda A.S. Mursinta (Journal of Language and Literature, 2018)
This study aimed to find out the translation procedures used by translator and the equivalence applied in the translation result of the poem. This study applied translation procedure theory from Vinay and Dalbernet (1995) and equivalence theory from Nida and Taber (1974). The data was taken from Ismail’s poems and the translated version by McGlynn. Each line of the poem was analyzed in order to find the category of translation procedures used and equivalence which focused on the meaning in the translation result. Some suggestions were also given when this study found some inappropriate translations. This study used qualitative method and primary research. The analysis result showed that the translator used some translation procedures while translating. There were single procedures used, such as literal translation, transposition, modulation, equivalence and adaptation. There were also multiple procedures used, such as modulation and reduction, transposition and modulation, transposition and expansion, literal translation and reduction, and literal translation and expansion. The most translation procedure used was literal translation. There were also  formal equivalence and dynamic equivalence in the translation result. The most equivalence used was dynamic equivalence. Keywords: poem, translation procedure, equivalence